Investigation of spermiotoxic, embryotoxic and cytotoxic effects of copper pyrithione on Paracentrotus lividus (Lamarck, 1816) - Taşcı, Ezgi; HAYRETDAĞ, SİBEL (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
Spermiotoxic, embryotoxic and cytotoxic effects of the widely used biofouling biocide copper pyrithione (CuPt) were evaluated in bioassays to examine the inhibition of fertilization rate, offspring quality and effects on early development of the sea urchin Paracentrotus lividus. CuPt was non-spermiotoxic for fertilization rates but the frequency of embryonic malformations increased in a concentration-dependent manner when eggs were fertilized with CuPt-exposed sperm. CuPt EC50 was calculated to be 13.58 μg/l for embryotoxicity. While the frequency of normally developed plutei decreased, the number of larvae with skeletal deformations increased. The IC25 and IC50 values in cytotoxicity assays were calculated to be 12.79 and 47.85 μg/l, respectively. The study revealed statistically significant decrease in the number of mitotically dividing cells, increase in the percentage of interphase cells and increased chromosomal abnormalities in the exposed cells. According to these results, CuPt can be said to have a highly toxic effect on sea urchin embryos at the applied concentrations. This situation suggests that there may be a potential risk of marine contamination with CuPt for this species.